2005
DOI: 10.1074/jbc.m411638200
|View full text |Cite
|
Sign up to set email alerts
|

The E46K Mutation in α-Synuclein Increases Amyloid Fibril Formation

Abstract: The identification of a novel mutation (E46K) in one of the KTKEGV-type repeats in the amino-terminal region of ␣-synuclein suggests that this region and, more specifically, Glu residues in the repeats may be important in regulating the ability of ␣-synuclein to polymerize into amyloid fibrils. It was demonstrated that the E46K mutation increased the propensity of ␣-synuclein to fibrillize, but this effect was less than that of the A53T mutation. The substitution of Glu 46 for an Ala also increased the assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
312
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(348 citation statements)
references
References 67 publications
28
312
0
3
Order By: Relevance
“…Previous studies have shown that -synuclein mutations (A53T, A30P, E46K) or triplications are associated with some autosomal-dominant PD [3][4][5][6] . Although there is no -synuclein gene mutation identified in idiopathic PD [7,8] , aggregated -synuclein has been found to be the major component of Lewy bodies and Lewy neurites, the pathological hallmarks of PD [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that -synuclein mutations (A53T, A30P, E46K) or triplications are associated with some autosomal-dominant PD [3][4][5][6] . Although there is no -synuclein gene mutation identified in idiopathic PD [7,8] , aggregated -synuclein has been found to be the major component of Lewy bodies and Lewy neurites, the pathological hallmarks of PD [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…␣-syn fibrils exhibit properties of amyloid (Spillantini et al, 1998), and ␣-syn assembles into amyloid fibrils in vitro (Han et al, 1995;Giasson et al, 1999), whereas SNCA mutations can accelerate ␣-syn fibrillization (Conway et al, 1998;Greenbaum et al, 2005). Therefore, it is plausible that ␣-syn misfolds and aggregates into amyloid fibrils that are neurotoxic and play a causative role in the pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…␣-Synuclein is a major protein component in Lewy bodies and Lewy neurites of sporadic PD (Spillantini et al, 1997(Spillantini et al, , 1998Spillantini and Goedert, 2000;Kahle et al, 2001;Kotzbauer et al, 2001;Forman et al, 2004). Three different mutations in the ␣-synuclein gene (A53T, A30P, and E46K) cause autosomal-dominant hereditary PD (Polymeropoulos et al, 1997;Farrer et al, 1998;Kruger et al, 1998;Zarranz et al, 2004;Greenbaum et al, 2005). Recent reports have shown that ␣-synuclein in Lewy bodies is hyperphosphorylated at S129, the major phosphorylation site of ␣-synuclein Hasegawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%